RAW 264.7 cell의 염증반응에 대한 散熱飮子의 항염증 효과 - 김태연(Tae Yeon Kim) (동의생리병리학회지, 2020)
Sanyeoleumja (SY) is the traditional Korean medicinal prescription for the treatment of inflammatory diseases of eyes. In this study, the anti-inflammatory effects of SY water extract were investigated. To measure the anti-inflammatory effects of SY, we examined the productions of inflammatory factor including nitric oxide (NO), prostaglandin E2 (PGE2), inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), interleukin-6 (IL-6), interleukin-1β (IL-1β) in lipopolysaccharide (LPS)-induced RAW 264.7 cells. SY inhibited NO and PGE2 production in a dose dependent manner and decreased the protein and mRNA expression of iNOS and COX-2. Also, SY decreased the mRNA expression of interleukin-6 (IL-6) and interleukin-1β (IL-1β). In conclusion, SY downregulated LPS-induced inflammatory factor productions, which could be a clinical basis for inflammatory diseases. KCI Citation Count: 0